PENGARUH PERFORMANCE GOALTERHADAP FLOW EXPERIENCEDALAM KONTEKS PERMAINAN ONLINE - Antonius Ricky Dewandono; Listyo Yuwanto; V. Heru Hariyanto (CALYPTRA, 2018)
Abstract - Indonesian online game industry hasn’t been receiving enough focus as of late, this leads to the domination of other countries’ international games inindonesia game market (Baskoro, 2015). The consequences would be bad for Indonesian game developer’s growth and competing power. This study focused onin games that cause an individual to had an optimal experience that is called flow. The purpose of this study is to provide clue for game developer to be able to create a more interesting game. In this study performance goal is seen as having potential to increase concentration which is very important for flow experience. Through experimental method of pretest-posttest control group design, we try to test the relationship between performance goal and flow to see whether the concentration enhancing characteristic of performance goal could affect flow experience, thus giving clue toward game developer for developing a successful product. With n = 30, the result shows that there is difference between experiment group being given performance goal to accomplish and the control group. This claim is proven by t score of 2.269 and p score of .031. The result also show a higher amount of flow experience occuring in experimental group. It can be concluded that by utilizing performance goal in games, the possibility for player to experience flow increase.